Breast, milk and microbes: a complex relationship that does not end with lactation. (July 2012) - Urbaniak, Camilla; Burton, Jeremy P; Reid, Gregor
Until relatively recently, the extent of microbiota presence in the human breast was under-appreciated. A high-throughput sequencing study and culture-based studies have demonstrated the extensive presence of microbes in human milk, with their origin believed to be from the skin, oral cavity and via gut translocation. Since formula milk substitutes do not contain these bacteria, what benefits are denied to these infants? The addition of probiotic bacteria to some infant formula is meant to provide some benefits, but these only contain one species and the dose is relatively high compared with breast milk. Many questions of importance to women's health arise from these findings. When, how and what types of microbes colonize the breast at different stages of a woman's life, including postlactation, and what effect do they have on the host in the short and long term? This article discusses some aspects of these questions.